Examining the Factors Influencing eWOM Through Social Networking Sites and the Effect of eWOM on Consumers’ Purchase Intention - Sharma, Jyakshi; Agarwal, Bhawna; Malati, N. (Indian Journal of Marketing, 2024)
Purpose : This study aimed to quantify the impact of electronic word-of-mouth (eWOM) on consumer purchase intention (PI), brand awareness (BA), and brand image (BI) by analyzing the variables influencing eWOM on social networking sites (SNSs). The preference of SNSs in relation to eWOM is another goal of this study. Methodology : A structured online questionnaire was utilized to gather information from 315 respondents who frequently utilized social media platforms. Using SmartPLS 4 software, partial least square-structural equation modeling (PLS-SEM) was used to evaluate the data. Findings : The findings revealed that out of six factors considered in the study to influence eWOM, four were found to influence eWOM positively. eWOM also had significant direct effects and indirect effects on BA, BI, and consumer PI. Furthermore, the current study highlighted preferred SNSs for eWOM. Instagram was found to be the most preferred site, followed by YouTube, Twitter, and then Facebook. Practical Implications : It was suggested that brands would boost user interaction, the company’s social media presence, and consumers’ propensity to purchase if they acknowledged the significance of particular factors influencing the eWOM channel and included it as a key component in their integrated communication strategy. Originality : Many empirical studies on the elements that directly influenced eWOM and its effect on consumer purchase intention have not been conducted despite the widespread use of online social networking. In order to close this gap, our study looked at four SNSs in order to determine the primary elements that directly influenced eWOM and to examine the direct and indirect effects of eWOM on purchase intention.